Identify Maths Learning Difficulties on the Set Subject - Alfiyansah, Ahmad Faris; Fitriani, Annisa; Narimoati, Hega; Handayani, Meli (Proceeding International Conference on Science and Engineering, 2020)
In conducting students’ learning activities that do not always work, there are often things that cause failure. The study aims to describe the difficulties students have experienced and to study the mistakes of the students in working on the tests in mathematics learning on the set subject. This type of research is a qualitative descriptive with a case study approach. Data collection techniques with problem instruments, interviews, and documentation. The legitimacy of data using technique triangulation. Data analysis through the data reduction phase, data presentation, and withdrawal of conclusions. The research was conducted with the subject of his research 30 students. The results showed that the type of difficulties experienced by students in the form of 1) difficulty in understanding the problem is the inability of the students to interpret the mathematical symbols on the subject of the set, 2) difficulty transforming that is the inability of students determining the set formula, 3) difficulty in the completion process is that students are not able to perform binary counting operations to solve the set problem. Then it can be concluded the types of difficulty learning mathematics that students experience in the subject of the association can be classified into 3 types, namely difficulty in understanding the problem, difficulty transforming the problem, and difficulty solving problems.